Successful Language Learners in an EFL context: an exploratory study of C2 level learners in an English language school in southern Spain - Jones, Christina (2016)
Abstract Despite the theory that significant exposure to a language, such as that experienced while living abroad, is necessary for mastery levels of achievement (Muñoz, 2008), learners who achieve proficiency purely through instructed foreign language settings (FLL) do exist. This dissertation used a mixed methods comparative case study design to explore successful adults learners enrolled in C2 level courses at a private language academy in southern Spain. A Complex Dynamic Systems perspective was taken in order to analyse connections between the biological, cognitive, psychological, behavioural and experiential variables that interact to influence their language development systems. I conclude that the success of these learners is related to the interaction between their experiences of self-efficacy, intrinsic motivation and their use of agency, all of which may be further moderated by cognitive or personality factors. Implications for FLL settings are also discussed.